The Christian Goddess : Archetype and Theology in the Fantasies of George MacDonald. - Gaarden, Bonnie (Rowman & Littlefield Pub. Group, 2011)
The Christian Goddess: Archetype and Theology in the Fantasies of George MacDonald examines the British Victorian writer's employment of female figures to represent Deity. Such symbolism is extremely unusual for a Christian author of this period andanticipates the efforts of many modern theologians to develop an image of God as Mother. Bonnie Gaarden reads the goddess-figures in MacDonald's fantasies as both archetypes of the collective unconscious and as emblems articulating MacDonald's unique Christian theology, which is Trinitarian, Neo-Platonic, mystical, and universalist. The goddesses be.